Bilateral Double Ureters with Bladder Neck Diverticulum in a Nigerian Woman Masquerading as an Obstetric Fistula - Imran O. Morhason-Bello; Sikiru A. Adebayo; Rukiyat A. Abdusalam; Oluwasomidoyin O. Bello; Kehinde H. Odubamowo; Olatunji O. Lawal; E. Oluwabunmi Olapade-Olaopa; Oladosu A. Ojengbede (Case Reports in Urology)
A 43-year-old woman presented with 20-year history of leakage of urine per vaginam. She had one failed repair attempt. Pelvic examination with dye test showed leakage of clear urine suggestive of ureterovaginal fistula. The preoperative intravenous urogram revealed duplex ureter and cystoscopy showed normally cited ureteric orifices with two other ectopic ureteric openings and bladder diverticula. The definitive surgery performed was ureteric reimplantation (ureteroneocystostomy) of the two distal ureteric to 2 cm superiolateral to the two normal orifices and diverticuloplasty. There was resolution of urinary incontinence after surgery. Three months after surgery, she had urodynamic testing done (cystometry), which showed 220 mLs with no signs of instability or leakage during filling phase but leaked on coughing at maximal bladder capacity. This is to showcase some diagnostic dilemma that could arise with obstetric fistula, which is generally diagnosed by clinical assessment.